2014
DOI: 10.1111/irv.12291
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of influenza to acute exacerbations of chronic obstructive pulmonary disease in Kashmir, India, 2010–2012

Abstract: We estimate the contribution of influenza to hospitalizations for acute exacerbations of chronic obstructive pulmonary disease (AECOPD) in Kashmir, India. Prospective surveillance for influenza among patients hospitalized with AECOPD was conducted at a tertiary care hospital. Patients had clinical data collected and nasal/throat swabs tested for influenza viruses. Outcomes among patients with and without influenza were compared with logistic regression adjusting for age and underlying conditions. During Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…As against the rest of the country with more tropical climate, the valley of Kashmir bound by the Himalayas has a temperate geography with respiratory tract illnesses predominating during the winter months, much like the northern hemispherical seasonality of respiratory viral illnesses seen in Northern America and Western Europe. We have earlier documented pandemic and seasonal influenza viruses as a cause of respiratory illness in Kashmir,3 , 4 that constitute the majority of hospital visits during the winter months, either as acute respiratory infections or as infective exacerbations of underlying chronic lung diseases like COPD 9. Sheri-Kashmir Institute of Medical Sciences (SKIMS) is a 820-bed facility in the summer capital, Srinagar, and constitutes the main tertiary referral centre for respiratory cases for the area.…”
Section: Methodsmentioning
confidence: 99%
“…As against the rest of the country with more tropical climate, the valley of Kashmir bound by the Himalayas has a temperate geography with respiratory tract illnesses predominating during the winter months, much like the northern hemispherical seasonality of respiratory viral illnesses seen in Northern America and Western Europe. We have earlier documented pandemic and seasonal influenza viruses as a cause of respiratory illness in Kashmir,3 , 4 that constitute the majority of hospital visits during the winter months, either as acute respiratory infections or as infective exacerbations of underlying chronic lung diseases like COPD 9. Sheri-Kashmir Institute of Medical Sciences (SKIMS) is a 820-bed facility in the summer capital, Srinagar, and constitutes the main tertiary referral centre for respiratory cases for the area.…”
Section: Methodsmentioning
confidence: 99%
“…Kashmir has a temperate geography in contrast with the generally more tropical climate in the rest of the country, and we have earlier reported a temperate seasonality of influenza virus circulation[56] which contributes to the exacerbations of COPD in 8% cases. [4] Demographic and clinical parameters were recorded in each case. Twin nasopharyngeal/oropharyngeal swabs were collected from the patients as described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…Twin nasopharyngeal/oropharyngeal swabs were collected from the patients as described earlier. [4] Tested for respiratory viruses including respiratory syncytial virus (RSV) A and B, parainfluenza (PIV) 1, 2, 3,[7] and 4,[8] human metapneumovirus (hMPV) A and B,[9] influenza A and B, enterovirus, corona NL65, OC43, and 229E viruses,[10] adenovirus 2 and 4,[11] rhinovirus,[10] and bocavirus,[12] were performed by in-house standardized duplex real time reverse-transcription polymerase chain reaction (qRT-PCR) using previously published primers and probes. The details of the enrollment and testing for influenza among these patients have been reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is evidence that viral infections lead to exacerbations of chronic airway diseases such as COPD [10,11], vaccination has not been proven to reduce mortality [12]. On the other hand, a systematic review that summarized the immunogenicity, safety, efficacy, and effectiveness of influenza vaccination in patients with COPD found that six of seven studies indicated long-term benefits such as decreased number of exacerbations, reduced number of hospitalizations, and decreased rates of all-cause and respiratory mortality [13].…”
Section: Discussionmentioning
confidence: 99%